PENGAPLIKASIAN PENDIDIKAN GIZI BAGI ANAK USIA DINI - Indi Dwi Utami; Yanti Ansari (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
The background to this problem is a lack of understanding about the application of nutritional health for early childhood. So the aim of this research was to find out food sources and how to apply them to young children. Application is a process or way of implementing nutrition education for early childhood. Not only children, parents also need to learn what foods contain lots of protein, fat, iron, minerals, carbohydrates, vitamins and so on, so that children can grow and develop well. Most parents only give their children food and provisions to school children without knowing the nutritional content in them, because children only know how to consume them. So it is the teacher's obligation to provide lessons about introducing nutritious food to children and parents. When snacking, pay attention to food hygiene so that you don't catch disease.